Exporters and wage inequality during the Great Recession: Evidence from Germany - Wolfgang Dauth; Hans-Joerg Schmerer; Erwin Winkler (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2015)
We analyze the evolution of the exporter wage premium (EWP) during the Great Recession and the resulting impact on wage inequality in Germany. Our results show that the EWP declined sharply between 2007 and 2008 and stagnated afterwards. This pattern is due to exporters starting to adjust their wage-setting one year earlier than non-exporters, likely due to the sharp decrease of foreign orders starting in late 2007. Finally, our decomposition shows that the fall of the EWP had a notable negative and persistent effect on wage inequality.
Keywords: F16; J31; 330; exporter wage premium; wage-inequality; Great Recession; international trade; matched employer-employee data